Degradable zinc-based layered heterostructure composite material with work-hardened soft layer and hard layer alternation as well as preparation method and application of degradable zinc-based layered heterostructure composite material
By introducing magnesium particles into zinc-based materials and using ARB technology to prepare zinc-based layered heterostructure composite materials, the shortcomings of zinc alloys in terms of mechanical properties, processing softening and aging are solved, and complementary strength and plasticity and hardening are achieved. Improvement of capabilities.
Patent Information
- Application Number
- CN202411608216.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-12
AI Technical Summary
Zinc alloys have shortcomings in mechanical properties, processing softening and aging, resulting in insufficient strength, processing softening and aging problems in implantable materials applications, affecting their stability and safety.
By introducing magnesium particles into the zinc-based material, a zinc-based layered heterostructure composite material with alternating soft and hard layers is prepared by cumulative stacking (ARB) technology, which improves its strength and work hardening ability.
The zinc alloy's strength and plasticity complement each other, significantly improves its work hardening ability, reduces the occurrence of aging, and improves the stability and safety of the material.
Smart Images

Figure CN119426363A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biodegradable zinc alloys, and particularly relates to a biodegradable zinc-based heterostructure composite material with alternating work-hardened soft and hard layers, and a preparation method and application thereof. Background Art
[0002] Zinc and its alloys have good biocompatibility and moderate degradation rate, and are considered to be the most promising biodegradable implant materials. However, in terms of mechanical properties, pure Zn has relatively low hardness, strength and plasticity. The tensile strength of cast pure Zn is only 30 MPa, and the elongation at break is only 2%. After plastic deformation treatments such as extrusion and rolling, the strength and plasticity of pure Zn are improved to a certain extent, but there is still a large gap with the mechanical property requirements of degradable implant materials. Therefore, improving the mechanical properties of Zn-based materials is the key to promoting their development and application.
[0003] Existing research results show that the mechanical properties of Zn-based materials can be greatly improved by alloying and combining appropriate plastic deformation treatment. Based on biocompatibility considerations, binary Zn alloys such as Zn-Cu, Zn-Ag, Zn-Mn, Zn-Mg, and Zn-Li, as well as multi-element Zn alloys such as Zn-Cu-Mg, Zn-Cu-Li, Zn-Cu-Ag, Zn-Ag-Mg, Zn-Ag-Mn, and Zn-Cu-Mn-Mg have been developed one after another. After deformation treatment, some alloys have reached or exceeded the mechanical property requirements of degradable implants. Among them, Zn-Li and Zn-Mg alloys have higher strength, while Zn-Cu, Zn-Ag, and Zn-Mn alloys show higher room temperature plasticity.
[0004] However, with the deepening of the research on zinc alloys, in addition to the problem of insufficient strength of zinc alloys, two other inherent deficiencies in the mechanical properties of zinc alloys have also attracted people's attention. That is, the work-softening behavior or insufficient work-hardening ability of zinc alloys, and the aging (self-ageing) phenomenon (that is, the plasticity of the alloy will be greatly reduced with the extension of room temperature storage time). The "work-softening" problem of zinc alloys may cause the stent to be unable to be firmly fixed on the balloon when it is pressed and gripped, and the stent is prone to displacement during the implantation and delivery process, resulting in failure to deliver to the correct lesion position where the support is to be released. At the same time, during the expansion of the stent, due to the weak work-hardening ability, it will cause uneven deformation, and even cause excessive deformation in the local position and fracture. The aging problem of zinc alloys will cause the stent to become brittle during service, so that the stent wire will suddenly break during the implantation and expansion process, and then cause medical accidents such as blocked blood vessels. These two problems have become bottlenecks restricting the clinical application of zinc alloys.
[0005] The processing softening and aging problems of zinc alloys are related to the low melting point of zinc. Due to the low melting point and poor thermal stability of zinc alloys, the alloys can experience solute atom segregation and precipitation at room temperature, or grain coarsening in the application environment, resulting in a serious decrease in the plasticity of the material. The low melting point of Zn allows it to directly undergo dynamic recrystallization (DRX) during cold deformation. On the one hand, DRX will lead to grain refinement and thus increase the yield strength, but this will make the yield strength close to the tensile strength, thereby reducing the work hardening ability; on the other hand, DRX leads to a decrease in the dislocation density inside the grains, which in turn leads to a continuous decrease in the resistance to plastic deformation, allowing Zn alloys to continue to deform, but difficult to harden and strengthen.
[0006] In order to solve the above problems, researchers have carried out a series of research work. For the aging problem of zinc alloys, the basic idea is how to increase the recrystallization temperature of zinc alloys or inhibit the occurrence of recrystallization. First, the recrystallization temperature of zinc alloys can be increased by alloying. For example, adding Ag or Cu elements to zinc alloys can greatly increase the recrystallization temperature of the alloy, so that the alloy exhibits good anti-aging ability. However, how to introduce suitable trace solute atoms through low-micro alloying means to improve the stability of grain boundaries (including twin boundaries) and dislocations by segregating at the grain boundaries (including twin boundaries) or dislocations (cores) of the Zn matrix requires in-depth research. The second is to introduce fine second-phase particles into zinc alloys to hinder the movement of grain boundaries, thereby inhibiting the recrystallization of the alloy. However, the presence of second-phase particles may promote or hinder the recrystallization of the base metal, depending on the size and distribution of the second-phase particles. Therefore, the research on the size, distribution and volume fraction of the second-phase particles on the twinning behavior, dynamic recrystallization process, texture and other aspects of zinc alloys needs to be systematically carried out. As for the problem of softening during processing, the solution is to reduce the a / c ratio through alloying, thereby promoting the initiation of non-basal slip in zinc alloys; the second is to introduce a bimodal structure material with fine grains and coarse grains through the regulation of the zinc alloy microstructure, in which the fine grains give the material strength through the back stress strengthening mechanism, while the coarse grains can provide the necessary work hardening rate and uniform elongation. However, these works are still in the initial stage, and there are few reports of successful cases.
[0007] The concept of heterogeneous materials was first proposed by Professor Zhu Yuntian and Professor Wu Xiaolei in 2015. With its unique structural characteristics and deformation mechanism, this type of material can achieve simultaneous improvement of material strength and plasticity. The basic structural characteristics of heterogeneous materials are that they are composed of microstructure units with significant strength differences, so there are a large number of soft / hard interfaces in the structure, and the regional size of the structural unit can vary from micrometers to millimeters. During the deformation of the material, a large strain gradient is generated near the interface of the structural unit, and additional heterogeneous deformation induced (HDI) strengthening is generated at these soft / hard interfaces. At the same time, a large number of geometrically necessary dislocations (GNDs) accumulated at the interface are conducive to improving the work hardening of the material.
[0008] Accumulative roll bonding (ARB) technology is an effective method for preparing layered heterogeneous materials. This technology has been successfully used to prepare a variety of composite materials with nano-layered structures such as Cu / Nb, Cu / Ta, Ti / Nb, etc., and their mechanical properties are far superior to those of any component unit. However, there has been no report on whether the ARB technology can be used to prepare zinc-based heterogeneous structural materials with alternating soft and hard layers in zinc alloys and achieve simultaneous improvement in the strength and work hardening properties of the alloy. Summary of the invention
[0009] In view of the shortcomings of the prior art, the first object of the present invention is to provide a method for preparing a degradable zinc-based layered heterostructure composite material (Zn / Mg layered composite material) with alternating soft and hard layers having high strength, good plasticity and significant work hardening ability. The preparation method of the present invention only adopts the cumulative rolling method to obtain the layered composite material, and the prepared composite material has the characteristic of high strength.
[0010] The second object of the present invention is to provide a degradable zinc-based heterogeneous structure composite material having alternating work-hardened soft and hard layers prepared by the above preparation method. The preparation method of the present invention is simple and controllable.
[0011] The third object of the present invention is to provide an application of a degradable zinc-based heterogeneous structure composite material having alternating work-hardened soft and hard layers prepared by the above preparation method.
[0012] In order to achieve the above object, the present invention adopts the following technical solution:
[0013] The present invention provides a method for preparing a degradable zinc-based heterogeneous structure composite material having alternating work-hardened soft and hard layers:
[0014] Step 1
[0015] A dispersion containing magnesium powder is applied to a zinc plate to obtain a zinc plate with a magnesium powder coating, and then two zinc plates with magnesium powder coatings are stacked to obtain a composite plate A, and the composite plate A is subjected to a single pass cold rolling to obtain a cold-rolled plate C, and the cold-rolled plate C is cut into two pieces from the middle, stacked, and then subjected to a single pass cold rolling, and the cutting-stacking-single pass cold rolling is repeated to obtain a magnesium particle reinforced zinc composite plate;
[0016] Step 2
[0017] The magnesium particle reinforced zinc composite plate obtained in step 1 is stacked with N zinc plates to obtain a composite plate B, the composite plate B is subjected to a single pass cold rolling to obtain a cold-rolled plate D, the cold-rolled plate D is cut into two pieces from the middle, stacked, and then subjected to a single pass cold rolling, the cutting-stacking-single pass cold rolling is repeated to obtain a layered composite plate, and finally a recrystallization annealing treatment is performed to obtain a degradable zinc-based layered heterogeneous structure composite material.
[0018] The preparation method of the present invention first coats pure magnesium (Mg) particles with good biocompatibility and degradability on the surface of pure zinc, adopts ARB technology to prepare a magnesium particle reinforced composite plate as a hard phase to provide strength and work hardening ability, then laminates it with a pure zinc plate, and then adopts the ARB method to prepare a layered composite plate in which soft (pure zinc) and hard (magnesium particle reinforced composite plate) layers alternately exist. The pure zinc plate provides ductility as a soft phase, and the difference in grain size of the two phases is used to construct a layered heterogeneous structure material with work hardening. Under the above synergy, the obtained composite material exhibits excellent work hardening ability, and at the same time, the strength and plasticity of the zinc alloy are complemented.
[0019] The inventors found that the selection of metal powder is also crucial. During the experimental exploration process, the inventors also tried Ag powder, Sn powder, etc., and found that the new phases they produced with zinc either could not pin the grain boundaries, or the effect of pinning the grain boundaries was not ideal, causing the mechanical properties of zinc to fail to meet the expected requirements.
[0020] In a preferred embodiment, in step 1, the dispersion containing magnesium powder is obtained by adding magnesium powder to acetone and ultrasonically dispersing the mixture for 10-20 minutes.
[0021] In actual operation, Mg powder is first stored in a vacuum environment for later use.
[0022] In a preferred embodiment, in step 1, the particle size of the magnesium powder is 20-25 μm.
[0023] Preferably, in step 1, the purity of the magnesium powder is ≥ 99.9%.
[0024] In a preferred embodiment, in step 1, the purity of the zinc plate is ≥ 99.9%.
[0025] In a preferred solution, in step 1, the zinc plate is first polished with a stainless steel wire brush having a wire diameter of 0.15-0.3 mm. The inventors found that the magnesium particle reinforced zinc composite plate obtained after rolling has the best bonding strength when the zinc plate is polished with a stainless steel wire brush having the above wire diameter.
[0026] According to a preferred embodiment, a dispersion containing magnesium powder is applied to one side of two zinc plates to obtain zinc plates with magnesium powder coatings, and then the two zinc plates with magnesium powder coatings are stacked, and during stacking, the contact surfaces of the two zinc plates are controlled to be the surfaces with magnesium powder coatings.
[0027] In a preferred embodiment, in step 1, when the composite plate A is subjected to a single pass cold rolling, the deformation is controlled to be 50%-60%.
[0028] In a preferred solution, in step 1, the cold-rolled sheet C is cut into two pieces from the middle, stacked, and then single-pass cold rolling is performed, and the cutting-stacking-single-pass cold rolling is repeated 4 times, and the deformation amount of any single-pass cold rolling is controlled to be 50%-60%. In the present invention, it is necessary to effectively control the number of rolling times in the preparation process of the magnesium particle reinforced zinc composite plate. If the number of rolling times is too much, the hard phase will be too brittle to continue the subsequent rolling.
[0029] In a preferred embodiment, in step 1, the mass fraction of magnesium in the magnesium particle reinforced zinc composite plate is 0.4-0.6%. In the present invention, the mass fraction of magnesium needs to be effectively controlled within the scope of the present invention. If the mass fraction of magnesium added is too low, the coating will be uneven. If the mass fraction of magnesium is too high, it will not be well combined with the zinc plate during rolling, resulting in delamination or failure to roll.
[0030] In a preferred solution, in step 1, the thickness of the magnesium particle reinforced zinc composite plate is 0.8-1 mm, preferably 0.9-1 mm; in step 2, the thickness of the zinc plate is 0.8-1 mm, preferably 0.9-1 mm.
[0031] In a preferred embodiment, in step 2, N is 1 or 2, preferably 1.
[0032] The inventors found that the ratio of soft and hard phases needs to be effectively controlled. When the ratio of soft phase (pure Zn plate): hard phase (Zn plate + Mg powder ARB4) = 1:1, it not only has excellent strength and ductility, but also has work hardening phenomenon. When the ratio of soft phase to hard phase is 1:2, due to the increase of hard phase, the strength increases, but the plasticity decreases, and the work hardening phenomenon is not obvious.
[0033] In the actual operation process of the present invention, the magnesium particle reinforced zinc composite plate and the zinc plate are placed in alcohol and ultrasonically cleaned for 10 minutes to remove surface grease. After air drying, the four corners of the alloy plate are drilled so that the composite plate can be fixed with copper wire before rolling. Then, a circular stainless steel brush is used to grind the adjacent contact surfaces of the alloy plates in parallel to the rolling direction to remove surface oxides and impurities. After grinding, the alloy plate is placed in acetone for ultrasonic cleaning to remove residual powder and other impurities.
[0034] In a preferred embodiment, in step 2, when the composite plate B is subjected to a single pass cold rolling, the deformation is controlled to be 50%-70%.
[0035] In a preferred embodiment, in step 2, the cold-rolled plate D is cut into two pieces from the middle, stacked, and then subjected to a single-pass cold rolling. The cutting-stacking-single-pass cold rolling is repeated 2-16 times, preferably 2-10 times, to obtain a layered composite plate, and the deformation amount of any single-pass cold rolling is controlled to be 50%-60%.
[0036] The inventors found that the cold-rolled plate is cut into two pieces from the middle, stacked, and then subjected to a single-pass cold rolling, and the cutting-stacking-single-pass cold rolling is repeated. During the repeated process, the deformation of the composite plate in the single-pass cold rolling is controlled within the above-mentioned range. This can make the alloy plates tightly bonded while avoiding cracking. The final degradable zinc-based heterogeneous structure composite material with work hardening ability has the best performance.
[0037] Preferably, in step 2, the temperature of the recrystallization annealing treatment is 100° C.-200° C., and the time of the recrystallization annealing treatment is 10-20 min.
[0038] The present invention also provides a degradable zinc-based heterogeneous structure composite material prepared by the above preparation method.
[0039] The present invention also provides the application of the degradable zinc-based heterostructure composite material prepared by the above preparation method, and the degradable zinc-based heterostructure composite material is used as a biodegradable implant material, and at the same time provides a new way to prepare a degradable Zn-based alloy with work hardening ability.
[0040] Beneficial Effects
[0041] The preparation method of the present invention first coats pure magnesium (Mg) particles with good biocompatibility and degradability on the surface of pure zinc, adopts ARB technology to prepare a magnesium particle reinforced composite plate as a hard phase to provide strength and work hardening ability, then laminates it with a pure zinc plate, and then adopts the ARB method to prepare a layered composite plate in which soft (pure zinc) and hard (magnesium particle reinforced composite plate) layers alternately exist. The pure zinc plate provides ductility as a soft phase, and the difference in grain size of the two phases is used to construct a layered heterogeneous structure material with work hardening. Under the above synergy, the obtained composite material exhibits excellent work hardening ability, and at the same time, the strength and plasticity of the zinc alloy are complemented.
[0042] The degradable zinc-based layered heterostructure composite material provided by the present invention forms a heterostructure in which a soft layer (pure Zn plate) and a hard layer (magnesium particle reinforced composite plate) coexist in the microstructure, wherein the soft phase mainly contributes to ductility, while the hard phase is responsible for enhancing strength and work hardening ability. Therefore, the layered composite material prepared by the present invention has a performance improvement of 380%-400% compared with the strength of the pure Zn plate after rolling. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.
[0044] Figure 1 This is a metallographic microstructure diagram of the Zn / Mg layered composite material obtained in the example after rolling 8 times.
[0045] Figure 2 This is a metallographic microstructure diagram of the Zn / Mg layered composite material obtained in the example after rolling 8 times.
[0046] Figure 3 This is a metallographic microstructure diagram of the Zn plate after being directly rolled 12 times in the manner of the embodiment.
[0047] Figure 4 The tensile stress-strain curves and corresponding tensile property data of the Zn / Mg layered composite material and pure Zn prepared in Example 1.
[0048] Figure 5 This is a SEM backscattered electron image of the Zn / Mg layered composite material prepared in Example 2 after 8-pass annealing. DETAILED DESCRIPTION
[0049] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0050] Example 1 (pure Zn plate: Zn+Mg powder composite plate = 1:1)
[0051] Step 1
[0052] Preparation of magnesium particle reinforced composite plate (Mg mass fraction is 0.5%):
[0053] First, two 1mm thick Zn plates with a purity of 99.9% were polished with a stainless steel wire brush with a wire diameter of 0.15-0.3mm; 25μm Mg powder was added to acetone and ultrasonically dispersed for 15min to obtain a dispersion containing Mg powder, and the dispersion containing Mg powder was applied to one side of the two Zn plates. After the acetone evaporated, the weight of the two Zn plates was weighed to determine the addition of Mg powder, and the mass fraction of Mg powder was controlled to be 0.5%. Then, the two Zn plates with magnesium powder coating were coated with 25μm Mg powder in acetone and ultrasonically dispersed for 15min to obtain a dispersion containing Mg powder. The zinc plates are stacked, and the contact surface of the two zinc plates is controlled to be the surface with magnesium powder coating during stacking; then cold rolling is performed, and the deformation is controlled to be 50% to obtain a 1 mm thick cold-rolled plate, and the cold-rolled plate D is cut into two pieces from the middle, stacked, and then single-pass cold rolling is performed, and the cutting-stacking-single-pass rolling is repeated 4 times to obtain a layered composite plate, and the deformation of the single-pass cold rolling in the repeated process is controlled to be 50%, to obtain a 1 mm thick magnesium particle reinforced composite plate, which provides strength and work hardening ability as a hard phase.
[0054] Step 2
[0055] Preparation of Zn / Mg layered composites
[0056] A 1mm thick Zn plate and a 1mm thick ZnMg alloy plate were cut into plates with a length of 55mm and a width of 30mm using a wire cutting machine. The cut plates were placed in alcohol and ultrasonically cleaned for 10 minutes to remove surface grease. After air drying, the four corners of the Zn plate and the alloy plate were drilled so that they could be fixed with copper wire. Then, a round stainless steel brush with a wire diameter of 0.3mm was used to grind the contact surface of the Zn plate and the ZnMg alloy plate parallel to the rolling direction to remove surface oxides and impurities. The polished Zn plate was placed in acetone and ultrasonically cleaned for 5 minutes to remove residual powder and other impurities. After completion, the ZnMg alloy plate was stacked with a Zn plate to obtain a composite plate, and copper wire was used to perforate and fix it to prevent the strips from sliding against each other. Then, a single pass cold rolling is performed using a two-roller rolling mill, and the deformation of the single pass cold rolling is controlled to be 50% to obtain a cold-rolled plate with a thickness of 1 mm. Then, the cold-rolled plate is cut into two pieces from the middle, stacked, and then single-pass cold rolling is performed, and the cutting-stacking-single-pass cold rolling is repeated 10 times. During the repeated process, the deformation of the single pass cold rolling is 50%, and a composite plate with a thickness of 1 mm is rolled. Then, the composite plate is annealed, and the annealing temperature is controlled to be 150° C., and the annealing time is 10 minutes. The present invention does not require any lubricant treatment, and repeated cold rolling completes the preparation of the final Zn / Mg layered composite material.
[0057] Specific data
[0058] 1. Figure 1 The metallographic microstructure of the Zn / Mg layered composite material obtained in Example 1 after 8 passes of rolling is shown in FIG. Figure 2 The metallographic microstructure of the Zn plate after being directly rolled 12 times in the manner of the embodiment. Figure 1 It can be seen that the Zn / Mg composite material after laminate rolling is mainly composed of gray striped Zn and white striped Mg, and the regions of Zn and Mg can be clearly distinguished, and the regions are continuous, uninterrupted, and evenly distributed in alternating fibers.
[0059] 2. Figure 3 The tensile deformation true stress-strain curves and corresponding tensile performance data of the Zn / Mg composite material obtained in Example 1 after 2, 4, 6, 8, and 10 annealing passes and pure Zn after 10 passes of rolling are shown. The tensile yield strength (YS), tensile ultimate strength (UTS), and elongation of the pure Zn plate after lamination rolling are 140MPa, 98MPa, and 53%, respectively. And it exhibits work softening characteristics. The tensile mechanical properties of the Zn / Mg layered composite material after lamination rolling show a significant improvement, and its tensile yield strength (YS), tensile ultimate strength (UTS), and elongation are 380MPa, 400MPa, and 15%, respectively, and the composite material exhibits work hardening characteristics.
[0060] 3. Figure 4 The SEM image of the Zn / Mg layered composite material obtained in Example 1 after 8 passes of rolling is shown in FIG. Figure 4 It can be seen that the Zn / Mg layered composite material after laminated rolling is mainly composed of a gray striped Zn layer and a black striped ZnMg layer. The regions of the Zn layer and the ZnMg layer can be clearly distinguished. The regions are continuous, uninterrupted, and alternately distributed in a fiber-like manner. It can be seen from the figure that the Zn layer is a large grain and the ZnMg layer is a small grain, thus forming a heterogeneous structure.
[0061] Example 2 (pure Zn plate: Zn+Mg powder composite plate = 1:2)
[0062] A 1mm thick Zn plate is placed between two 1mm thick ZnMg alloy plates prepared in the embodiment and cut into plates with a length of 55mm and a width of 30mm using a wire cutting machine. The cut plates are placed in alcohol and ultrasonically cleaned for 10 minutes to remove surface grease. After air drying, the four corners of the Zn plate and the alloy plate are drilled so that they can be fixed with copper wire. Then, a round stainless steel brush with a wire diameter of 0.3mm is used to grind the contact surface of the Zn plate and the ZnMg alloy plate parallel to the rolling direction to remove surface oxides and impurities. The polished Zn plate is placed in acetone and ultrasonically cleaned for 5 minutes to remove residual powder and other impurities. After completion, the ZnMg alloy plate is stacked with a Zn plate to obtain a composite plate, and is fixed with copper wires to prevent the strips from sliding against each other. Then, a single pass cold rolling is performed using a two-roller rolling mill, and the deformation of the single pass cold rolling is controlled to be 66% to obtain a cold-rolled plate with a thickness of 1 mm. Then, the cold-rolled plate is cut into two pieces from the middle, stacked, and then single-pass cold rolling is performed, and the cutting-stacking-single-pass cold rolling is repeated 10 times. During the repeated process, the deformation of the single pass cold rolling is 50%, and a composite plate with a thickness of 1 mm is rolled. Then, the composite plate is annealed, and the annealing temperature is controlled to be 150° C., and the annealing time is 10 minutes. The present invention does not require any lubricant treatment, and repeated cold rolling completes the preparation of the final Zn / Mg layered composite material.
[0063] In the Zn / Mg layered composite material provided in this example, the ratio of pure Zn plate to Zn+Mg powder composite plate is 1:2.
[0064] Performance Testing
[0065] Figure 5The tensile deformation true stress-strain curves and corresponding tensile performance data of the Zn / Mg composite material obtained in Example 2 after rolling 2, 4, 6, 8, 10 passes and annealing and rolling 10 passes. Due to the increase in the proportion of the Zn+Mg powder composite plate, the strength of the layered composite material after lamination rolling is significantly improved, and its tensile yield strength (YS), tensile ultimate strength (UTS), and elongation are 480MPa, 470MPa, and 8%, respectively. The composite material does not show obvious work hardening characteristics and its plasticity is slightly different from that of Example 1.
[0066] Comparative Example 1
[0067] The other conditions were the same as those in Example 1, except that the ratio of pure Zn plate: Zn+Mg powder composite plate was adjusted to 2:1. The obtained composite plate was rolled 8 times and then recrystallized annealed at the same temperature. Its tensile yield strength (YS) and tensile ultimate strength (UTS) were 280 MPa and 270 MPa, respectively.
[0068] Comparative Example 2
[0069] The other conditions are the same as those in Example 2, except that a 2 mm thick Zn plate is placed between two 1 mm thick ZnMg alloy plates. The obtained composite plate is rolled 8 times and then recrystallized annealed at the same temperature. The tensile yield strength (YS) and tensile ultimate strength (UTS) are 390 MPa and 370 MPa, respectively. While the plasticity is reduced, its work hardening characteristics are not obvious.
Claims
1. A method for preparing a degradable zinc-based heterostructure composite material having alternating work-hardened soft and hard layers, characterized in that: Step 1 A dispersion containing magnesium powder is applied to a zinc plate to obtain a zinc plate with a magnesium powder coating, and then two zinc plates with magnesium powder coatings are stacked to obtain a composite plate A, and the composite plate A is subjected to a single pass cold rolling to obtain a cold-rolled plate C, and the cold-rolled plate C is cut into two pieces from the middle, stacked, and then subjected to a single pass cold rolling, and the cutting-stacking-single pass cold rolling is repeated to obtain a magnesium particle reinforced zinc composite plate; Step 2 The magnesium particle reinforced zinc composite plate obtained in step 1 is stacked with N zinc plates to obtain a composite plate B, the composite plate B is subjected to a single-pass cold rolling to obtain a cold-rolled plate D, the cold-rolled plate D is cut into two pieces from the middle, stacked, and then subjected to a single-pass cold rolling, the cutting-stacking-single-pass cold rolling is repeated to obtain a layered composite plate, and finally a recrystallization annealing treatment is performed to obtain a degradable zinc-based layered heterogeneous structure composite material.
2. The method for preparing a degradable zinc-based heterostructure composite material having alternating work-hardened soft and hard layers according to claim 1, characterized in that: In step 1, the magnesium powder-containing dispersion is obtained by adding magnesium powder to acetone and ultrasonically dispersing for 10-20 minutes; In step 1, the particle size of the magnesium powder is 20-25 μm; In step 1, the purity of the magnesium powder is ≥ 99.9%; In step 1, the purity of the zinc plate is ≥ 99.9%; In step 1, the zinc plate is first polished with a stainless steel wire brush with a wire diameter of 0.15-0.3 mm.
3. The method for preparing a degradable zinc-based heterostructure composite material having alternating work-hardened soft and hard layers according to claim 1 or 2, characterized in that: A dispersion containing magnesium powder is brushed on one side of two zinc plates to obtain a zinc plate with a magnesium powder coating, and then the two zinc plates with the magnesium powder coating are stacked, and during the stacking, the contact surface of the two zinc plates is controlled to be the surface with the magnesium powder coating.
4. The method for preparing a degradable zinc-based heterostructure composite material having alternating work-hardened soft and hard layers according to claim 1 or 2, characterized in that: In step 1, when the composite plate A is subjected to single-pass cold rolling, the deformation is controlled to be 50%-60%; In step 1, the cold-rolled sheet C is cut into two pieces from the middle, stacked, and then single-pass cold rolling is performed. The cutting-stacking-single-pass cold rolling is repeated 4 times, and the deformation amount of any single-pass cold rolling is controlled to be 50%-60%.
5. The method for preparing a degradable zinc-based heterostructure composite material having alternating work-hardened soft and hard layers according to claim 1 or 2, characterized in that: In step 1, the mass fraction of magnesium in the magnesium particle reinforced zinc composite plate is 0.4-0.6%.
6. The method for preparing a degradable zinc-based heterostructure composite material having alternating work-hardened soft and hard layers according to claim 1 or 2, characterized in that: In step 1, the thickness of the magnesium particle reinforced zinc composite plate is 0.8-1 mm; in step 2, the thickness of the zinc plate is 0.8-1 mm; In step 2, N is 1 or 2.
7. The method for preparing a degradable zinc-based heterostructure composite material having alternating work-hardened soft and hard layers according to claim 1 or 2, characterized in that: In step 2, when the composite plate B is subjected to single-pass cold rolling, the deformation is controlled to be 50%-70%; In step 2, the cold-rolled sheet D is cut into two pieces from the middle, stacked, and then single-pass cold-rolled. The cutting-stacking-single-pass cold-rolling is repeated 2-16 times to obtain a layered composite plate, and the deformation amount of any single-pass cold rolling is controlled to be 50%-60%.
8. The method for preparing a degradable zinc-based heterostructure composite material having alternating work-hardened soft and hard layers according to claim 1 or 2, characterized in that: In step 2, the temperature of the recrystallization annealing treatment is 100° C.-200° C., and the time of the recrystallization annealing treatment is 10-20 minutes.
9. A degradable zinc-based heterogeneous structure composite material prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the degradable zinc-based heterostructure composite material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The degradable zinc-based heterogeneous structure composite material is used as a biodegradable implant material.
Citation Information
Patent Citations
Preparation method of high-strength Zr-based alloy composite material
CN111203443A
High-entropy alloy particle reinforced metal matrix composite material and preparation method thereof
CN111672906A
Layered magnesium-magnesium-based composite material plate as well as preparation method and application thereof
CN114134302A
Magnesium / aluminum layered composite board with high modulus and high damping and preparation method thereof
CN118664974A
Production method for aluminum-dispersed reinforced copper strip
JP2003001302A